Resident’s Perception of Safety in Planned Residential Neighborhood of Kathmandu - Shrestha, Rachana; Uprety, Sanjaya (Journal of Engineering Technology and Planning, 2019)
Kathmandu valley has been urbanizing rapidly but the planning of neighborhoods is limited to land readjustments and housing developments. The focus of such development is to provide either the service plots or ready to move in housing stock. Residential Environment Satisfaction (RES) has been used as a concept to measure the perceptual dimension neighborhood planning. Moreover, neighborhood safety is a key priority while considering RES. This paper aims to examine the relationships between various factors related to the safety as a measure of the RES in the planned residential neighborhood in Kathmandu Valley. Since the planned cities or communities seem to have better residential satisfaction, the case study area surveyed upon is Purano Sinamangal Town planning, a land pooling area nearly at junction to three major districts of Kathmandu valley. Various factors have been taken as a measure for neighborhood safety including physical and socio-psychological variable. This research is based on a mixed method. A figure of 109 households was determined as sample household size and individual representatives were interviewed for the survey. The research finds that perception of safety is very high depending on the ethnic groups while it is also significant in case of occupation that the respondent holds. The reason for safety highly was found to be dependent upon good street design, the presence of good neighbors and provision of security patrols. Also, annoyance factors such as disturbances from street and vehicles, crimes, neighborly disputes were found to make the neighborhood unsafe. The research concludes that safety is a major concern for RES and it had been perceived by the residents through significant of good neighborly relation and safety measures in road planning and design.